Édito - Étudier les pratiques se réclamant des pédagogies différentes à l’école primaire : un enjeu pour les sciences de l’éducation et de la formation - Bruno Robbes; Sébastien Pesce (Recherches en Éducation)
Starting from the relationship between pedagogy and educational research, this editorial clarifies the notions of pedagogy, different and alternative pedagogies. It then takes up the already established observation that little research is devoted to these pedagogical practices, wondering whether educational sciences are neglecting their study. On the contrary, the articles in this dossier suggest that there are still researchers in education who are interested in these subjects. They reopen essential debates for these sciences at a time when, in the field of education, emerging currents of educational research are claiming to revolutionize pedagogy through neuro-education, neuro-pedagogy or direct instruction, based on the paradigm of the “school effectiveness” derived from Evidence-Based research. These debates are at the heart of the dossier's problematic: what methodologies, epistemologies and disciplinary and theoretical frameworks are used by educational sciences to study the teaching/learning practices of elementary school and classrooms claiming to follow “different” pedagogies?